The Badger eXploration Loft at Desert RATS 2011 - Wachs, Jordan (Proceedings of the Wisconsin Space Conference, 2012)
In recent years, the aim of both NASA as well as the nascent private space industry has become increasingly audacious. By any measure, it is becoming apparent that long duration manned missions to deep space are inevitable; as are the inherent complexities and risks associated with such large scale undertakings. With this in mind, it is critical that engineers and scientists work toward the goal of understanding the difficulties that lay ahead. Analog studies such as the Desert Research and Technology Studies (D-RATS) are one critical resource available for the investigation of the effectiveness of various mission architectures. This paper provides a brief outline of D-RATS and focuses on the role, abilities, and benefits of the integration of the Badger X-Loft with the Habitat Demonstration Unit mission during D-RATS 2011.Â 